ADVANTAGES AND DISADVANTAGES OF ONLINE EDUCATION (American Journal of Pedagogical and Educational Research, 2023)
Education is a fundamental aspect of personal and professional development, and with the advancements in technology, the options for pursuing education have expanded significantly. Two main forms of education that have emerged are online education and traditional offline education. Both these forms have their own advantages and disadvantages. In this article, we will explore some of these advantages and disadvantages of online and offline education.